0053 Developing peer role-play as an effective tool for learning. (2nd November 2015) - Armstrong, Ailsa; Williamson, Maureen; Young, Fiona; Gale, Michael
Abstract : Background: Role-play and simulated patients (SP) are widely used tools to aid the development of effective communication skills within the medical curriculum. Joyner and Young 1 identified that peer role-play allows students to practice their clinical, diagnostic and patient management skills. Bosse et al . 2 noted this led to significantly better OSCE performance. Burgess et al . 3 identified that acting as a SP was perceived as a positive experience by peer medical students. Within the Clinical Skills Centre, Inverness, a formative OSCE is run for the 5 th year medical students on clinical placement from the University of Aberdeen. The majority of SP's are retired professionals, thus limiting the realism of the simulation for more complex scenarios involving younger patients. Given the difficulties in communication with younger adult patients we were interested in developing a solution which allowed the students to confront this issue. As a result, we asked 4 th year medical students for volunteers to act as SP's for specific OSCE scenarios. Description of innovation: The aim of this project is to evaluate the student's experience of participating as a SP in terms of their own OSCE performance. We are keen to develop this further by evaluating if their learning and clinical skills performance improved when faced with similar scenarios to those they performed as a SP. What improvements occurred?: At the first iteration, students underwent informal scenario discussion but an hour-long formal session is now provided to ensure they are adequately prepared. The initial pilot established that all students found it a positive experience. Take home messages: At the time of writing, these 4 th year medical students have been involved in two formative OSCEs and early feedback from them identifies it has been beneficial both in terms of their own learning and in understanding the patients' perspective. References: Joyner B, Young L. Teaching medical students using role play: Twelve tips for successful role plays. Med Teach 2006;28(3):225–229 Bosse HM, Schultz J, Nickel M, Lutz T, Moltner, A. Junger J, Huwendiek S, Nikendei C. The effect of using standardized patients or peer role play on ratings of undergraduate communication training: a randomized controlled trial. Patient Educ Couns 2012;87:300–306 Burgess A, Clark, T, Chapman R, Mellis C. Medical student experience as simulated patient's in the OSCE. Clin Teach 2013;10:246–250